STRATEGI DAKWAH TGH. IRHAM FAHMI DALAM MEMBENTUK MASYARAKAT YANG RELIGIUS DI DESA BATU NGULIK KECAMATAN PRAYA LOMBOK TENGAH - Isnawati Isnawati (Lembaga Sepercenter, 2026)
The development of a religious society requires appropriate da'wah strategies to ensure that Islamic values are understood and practiced in everyday life. This study aims to analyze the da'wah strategies implemented by Tgh. Irham Fahmi in fostering a religious community in Batu Ngulik Village, Praya District. This study employed a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that Tgh. Irham Fahmi implemented three da'wah strategies, namely bil-lisan (verbal preaching), bil-hal (preaching through exemplary actions), and bil-mal (preaching through charitable giving). The bil-lisan strategy was carried out through regular religious gatherings held twice a week, covering topics such as Qur'anic interpretation, Islamic morals, and Islamic jurisprudence. The bil-hal strategy was demonstrated through exemplary conduct in worship, polite communication, and a modest lifestyle, which encouraged positive behavioral changes among community members, particularly young people, to become more active in worship and to exhibit better moral conduct. Meanwhile, the bil-mal strategy was implemented through monthly financial assistance for orphans and underprivileged families, house renovation support for low-income residents, and the provision of clean drinking water facilities for the local community. The findings indicate that the integrated implementation of these three strategies has enhanced religious understanding, strengthened religious values, and promoted positive behavioral changes toward a more religious society. These findings suggest that da'wah strategies integrating effective communication, exemplary conduct, and social concern are effective in fostering a religious community.